A Brief Note on "Hellenistic Formal Receptions and Paul's Use of AΠANTHΣIΣ in 1 Thessalonians 4:17" - Gundry, Robert Horton (Bulletin for biblical research, 1996)
This brief essay responds to an earlier essay by Michael R. Cosby (BBR 4 [1994] 15–34) which has created some confusion with respect to the meaning of ἀπάντησις in Thess 4:17. The parallels between Paul's description of the Parousia of Jesus in 1 Thess 4:15–17 and those of Hellenistic formal receptions are closer than Cosby allows. It is probable that Paul's use of ἀπάντησις does indeed reflect such Hellenistic customs and traditions.